Numerical Simulations of Transfer of Spatial Beam Aberrations in Optical Parametric Chirped-Pulse Amplification - Ying Chen; Yuan Zhou; Guobao Jiang; Lulu Wang (Advances in Condensed Matter Physics)
In this paper, the spatial characteristics of the optical parametric chirped-pulse amplification (OPCPA) process were numerically studied when initial pump beam was aberrated. Numerical results showed that the spatial walk-off effect transferred phase modulation partly to the signal beam as the pump phase was modulated. Moreover, the modulation amplitude became increasingly severe as the nonlinear length extended. In the absence of phase aberration in the initial input signal, the induced phase aberration in the output signal was assumed as the differential form of the pump beam phase. As the pump beam intensity was modulated, the spatial walk-off effect reduced the influence of pump beam noise on beam quality and the angular spectrum but reduced signal gain simultaneously; thus, it may do more harm than good in the OPCPA process. In the case of a non-diffraction-limited pump beam, the greater the beam quality factor Mp2, the lower the conversion efficiency of the output signal in the OPCPA process. These results have important guiding significance for optimized design of an OPCPA system for high power laser.